Riwayat Penyakit Kardiovaskuler Dan Kejadian Happy Hypoxia Pada Pasien Suspek Covid-19 - Wahyu Dini Metrikayanto; Novita Dewi; Rachmat Chusnul Choeron (Universitas Tribhuwana Tunggadewi, 2021)
ABSTRACT Happy Hypoxia is one of the symptoms of Covid-19 that is often not known by society. This condition is often found in cases of Covid-19 with very low oxygen levels in the blood. Happy Hypoxia can be fatal with the failure of several organs of the body. The purpose of this study was to determine the relationship between the incidences of happy hypoxia in suspected Covid-19 patients with a history of cardiovascular disease at the ER Panti Waluya Hospital, Malang. The design of this study was cross sectional with a total sample of 18 Covid-19 patients selected using the Total Sampling technique. Data about Happy Hypoxia and history of cardiovascular disease were taken based on secondary data from Medical Records in the ER Panti Waluya Hospital, Malang. Based on the results of the Fisher Exact Test, it was found that p = (0.0477) (0.050) so H1 was rejected, meaning that there was no relationship between the incidence of happy hypoxia in suspected Covid-19 patients with a history of cardiovascular disease in the ER Panti Waluyo Hospital, Malang City. This means that the incidence of happy hypoxia in Covid-19 patients is not only related to cardiovascular disease Keywords: cardiovascular desease, covid-19, happy hypoxia ABSTRAK Salah satu gejala Covid-19 yang sering tidak diketahui oleh masyarakat umum adalah happy hypoxia. Kondisi ini sering ditemukan kasus Covid-19 dengan kadar oksigen dalam darah sangat rendah sehingga bisa berdampak pada terjadinya pingsan atau bisa berakibat fatal juga dengan adanya kekagalan beberapa organ organ tubuh. Tujuan dari penelitian ini adalah untuk mengetahui Hubungan Kejadian Happy Hypoxia Pada Pasien Suspek Covid-19 Dengan Riwayat Penyakit Cardiovaskuler Di UGD Rs Panti Waluya Malang. Desain penelitian ini menggunakan cross sectional dengan jumlah sampel sebanyak 18 pasien Covid-19 yang dipilih dengan tekhnik Total Sampling. Data tentang Happy Hypoxia dan riwayat penyakit kardiovaskuler diambil berdasarkan data sekunder dari Rekam Medik di UGD RS Panti Waluya Malang. Berdasarkan hasil uji Fisher Exact Test didapatkan p = (0,477)(0,050) sehingga H1 ditolak, artinya tidak ada Hubungan Kejadian Happy Hypoxia Pada Pasien Suspek Covid-19 Dengan Riwayat Penyakit Kardivaskuler Di UGD RS Panti waluyo Kota Malang.. Hal ini memberikan makna bahwa kejadian happy hypoxia pada pasien Covid-19 tidak hanya berkaitan dengan penyakit kardiovaskuler. Kata kunci: Covid-19, Happy hypoxia, Penyakit Kardiovaskuler